Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai Negeri Sipil pada Badan Perencanaan Pembangunan Daerah (Bappeda) Kabupaten Bungo - Yudhi Novriansyah; Suci Sabilah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of Leadership and Work Environment on the Performance of Civil Servants at the Regional Development Planning Agency (Bappeda) of Bungo Regency. The type of research conducted is quantitative research using the purposive sampling technique. The sample used in this study consisted of 30 respondents. The data from this research were processed and analyzed using Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Test with the help of SPSS version 26 software.The research results state that Leadership affects the Performance of Civil Servants where t-count (2.385) > t-table (2.051) and is significant because (0.024 < 0.05). Work Environment affects the Performance of Civil Servants where t-count (3.211) > t-table (2.051) and is significant because (0.003 < 0.05). Meanwhile, simultaneously, the independent variables affect the dependent variable where F-count 9.952 > F-table of 3.34 with a probability level (0.000 < 0.05). The Coefficient of Determination (R2) value is 42.4%, with the remaining influenced by other dimensions. Through this research, it is useful to enhance knowledge and insights related to Leadership and Work Environment on the Performance of Civil Servants.